Public Access to Federally Funded Scientific Research: Building Communities of Collaboration. - Janice Young (Issues in Science and Technology Librarianship, 2015)
The author comments on a federal initiative implemented by the U.S. Department of Energy (DOE) Office of Scientific and Technical Information (OSTI) that allows public access to federally funded scientific research. Topics discussed include the impact of scholarly scientific literature on programming gaps in curriculum development and on students' critical thinking development, as well as her recollections of volunteering as a Civility Award Judge for the 2015 Tennessee Science Bowl.